2020
DOI: 10.1097/mao.0000000000002589
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception Gap Is Predictive of an Active Middle Ear Implant Advantage

Abstract: Objective: Evaluate whether the difference between word recognition score (WRS) obtained unaided under earphone and with a hearing aid (HA), the speech perception gap (SPgap), is predictive of performance with a totally implantable active middle ear implant (AMEI). Study Design: Retrospective review of systematically collected data. Setting: Private otologic practice. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In the Shohet et al (9) retrospective study, 86% of the 133 subjects demonstrated a SPgap pre-operatively with their appropriately fit CHA, reinforcing that CHA users often do not reach their cochlear potential. The average SPgap of CHA users pre-operatively in this study was 24.7% compared to 3.0% once they received their AMEI.…”
Section: Candidacy Developmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Shohet et al (9) retrospective study, 86% of the 133 subjects demonstrated a SPgap pre-operatively with their appropriately fit CHA, reinforcing that CHA users often do not reach their cochlear potential. The average SPgap of CHA users pre-operatively in this study was 24.7% compared to 3.0% once they received their AMEI.…”
Section: Candidacy Developmentsmentioning
confidence: 98%
“…A second vertical reference line at 18 shows the Earphone-HA speech perception gap at and beyond which >85% of subjects perform better with the AMEI than with their HA. From Shohet et al ( 9 ).…”
Section: Candidacy Developmentsmentioning
confidence: 99%
“…For patients with only SNHL, the value of preoperative air conduction threshold and the maximum recognition score of monosyllables via earphones must be analyzed. One positive predictor for better speech understanding with an active middle ear implant in cases of SNHL compared to conventional hearing aids turned out to be the speech perception gap with a conventional hearing system at a basic speech level (50 dB or 65 dB SPL) and the maximum speech understanding measured via earphones [63,121,122]. The maximum word recognition score in the speech audiogram should nearly be achieved at 65 dB with a conventional hearing system.…”
Section: Consideration Of Potential Influencing Factors On Speech Per...mentioning
confidence: 99%
“…Als positiver Prädiktor für ein besseres Sprachverstehen mit einem aktiven Mittelohrimplantat bei SNHL gegenüber der konventionellen Hörsystemversorgung wurde die Diskrepanz des Sprachverstehens (engl. Speech Perception Gap) mit einem konventionellen Hörsystem bei einem festen Sprachschallpegel (50 dB oder 65 dB SPL) und dem über Kopfhörer gemessenem maximalen Sprachverstehen herausgestellt [63,121,122]. Das maximal erreichte Sprachverstehen im Sprachaudiogramm sollte mit einem konventionellen Hörsystem bereits bei 65 dB annähernd erreicht werden.…”
Section: Aktive Mittelohrimplantate In Der Pädaudiologieunclassified